WEB-BASED GEOGRAPHIC INFORMATION SYSTEM OF BANTEN PIODALAN STORES MAPPING IN DENPASAR CITY - I Made Gede Sunia Pradnyantara; Dwi Putra Githa; Gusti Agung Ayu Putri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Banten is a medium used in Hindu religious ceremonies and also as a medium of prayer in getting closer to Ida Sang Hyang Widhi Wasa or God Almighty. Hindus are required to be able to know the meaning and method of making a banten, but along with the development of an increasingly modern era resulting in a high level of activity in big cities, one of which is Denpasar City, this underlies the tendency of people to prefer buying banten rather than making it. because of the limited time they have. This also underlies the development of a web-based mapping information system for banten piodalan stores in the city of Denpasar. The public will find it easy to find out the mapping of the locations of Banten shops in the city of Denpasar through the system. The system is also equipped with a marketplace feature that makes it easy for the public to make transactions to buy banten piodalan they want and those who want to make transactions in selling banten piodalan.